Faktor Fundamental, Non Fundamental, Kinerja Perusahaan dan Good Corporate Governance sebagai Variabel Intervening - A'ini, Sherly Qurrota; Suwandi, Suwandi (E-Jurnal Akuntansi, 2023)
The phenomenon of fluctuating stock prices causes company performance to fluctuate, this is an interesting issue to research. The aim of this research is to identify fundamental and non-fundamental factors that influence company performance with Good Corporate Governance (GCG) as an intervening variable. The research population of basic & chemical industrial companies in 2019-2022, the sample that complied with the purposive sampling technique was 74 companies with 296 observational data processed using PLS to analyze the data. The results of the research analysis and discussion findings show that fundamental factors have a negative influence on Good Corporate Governance , fundamental factors have a negative effect on company performance, and Good Corporate Governance has an effect on company performance. Keywords: Company Performance; Fundamental Factors; Non-Fundamental Factors; GCG